RANCANG BANGUN SISTEM MONITORING TEGANGAN, ARUS, DAN KECEPATAN MOBIL LISTRIK AGNIJAYA WEIMANA - Adyana Putra, I Kadek; Satya Kumara, I Nyoman; Raka Agung, I G A Putu (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUM, 2023)
Electric energy can be utilized as an alternative to replace oil-based fuel. One of the steps to address the energy crisis issue is through the Energy-Efficient Car Competition (KMHE), which emphasizes the energy efficiency of vehicles. The WEIMANA team from Udayana University has participated in the Urban Concept category by designing a vehicle named Agnijaya. Agnijaya is an electric-powered car that uses a Brushless DC (BLDC) electric motor. Currently, the Agnijaya electric car does not have a continuous monitoring system for voltage, current, and speed. The research aims to design a monitoring system for the Agnijaya electric car using an SD card as a data storage medium for voltage, current, and speed data. This system is controlled using an Arduino Mega 2560 Pro Mini microcontroller board as the data processor and an SD card as the data storage medium. The monitoring system for the Agnijaya electric car has been successfully designed, built, and tested for voltage, current, and speed values. Testing was conducted by comparing the measured values of voltage, current, and speed, all of which were stored on the SD card. The results of the analysis indicate that the percentage deviation in battery voltage measurement is 0.85%, the deviation in battery current measurement is 0.23%, and the deviation in speed measurement is 0.32%.